Application of Arabic language communication model in teaching and learning of Islamic Education - Suhid, A.; Mutalib, L.A.; Ahmad, A.M. (IDOSI Publications, 2012)
Arabic language is considered as a special language, at least for Muslims, as it is the language of the Qur’an. Therefore the language has been given emphasis in Islamic education system. In fact, it is not only introduced in religious stream schools but also in daily secondary schools as an elective subject. Realizing the important of Arabic language, the Ministry of Education, Malaysia through the Islamic and Moral Education Department has introduced Arabic Language Communication Model in the j-QAF programme.It was initially implemented at primary school level in year 2005 and now has almost completed a round of its implementation.As the Arabic Language Communication Model is still newly introduced, a research to identify the effectiveness of its implementation has been conducted. 309 j-QAF teachers in Selangor state were involved in this research. The quantitative data gained were analysed using the Statistical Package for The Social Science(SPSS) programme. Besides discussing the research findings, the researchers also analysed the problems faced in the implementation of the Arabic language Communication Model and a few suggestions have also been highlighted.